Discourses, Modes, Media and Meaning in an Era of Pandemic : A Multimodal Discourse Analysis Approach - Sabine Tan; Marissa K. L. E (Routledge, 2023)
The COVID-19 pandemic has affected all aspects of our everyday lives – from the political to the economic to the social. Using a multimodal discourse analysis approach, this dynamic collection examines various discourses, modes and media in circulation during the early stages of the pandemic, and how these have impacted our daily lives in terms of the various meanings they express. Examples include how national and international news organisations communicate important information about the virus and the crisis, the public's reactions to such communications, the resultant (counter-)discourses as manifested in social media posts and memes, as well as the impact social distancing policies and mobility restrictions have had on people's communication and interaction practices. The book offers a synoptic view of how the pandemic was communicated, represented and (re-)contextualised across different spheres, and ultimately hopes to help account for the significant changes we are continuing to witness in our everyday lives as the pandemic unfolds.This volume will appeal primarily to scholars in the field of (multimodal) discourse analysis. It will also be of interest to researchers and graduate students in other fields whose work focuses on the use of multimodal artefacts for communication and meaning making.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.